Interventions for zoster-associated pain: A retrospective study based on the clinical database - Chen, Lu; Li, Jun; Liu, Hui; Yang, Pingliang; Zuo, Yunxia; Ye, Ling (Frontiers in Neurology, 2022)
Background: Herpes zoster-associated pain can lead to severe pain and reduced quality of life. Exploring effective treatment and the risk factors of zoster-associated pain has become important. Methods: Interventions including nerve block, radiofrequency and thermocoagulation were used for zoster-associated pain. The data of 131 patients with herpes zoster and 230 patients with postherpetic neuralgia was collected at 2 weeks, 3 months, 6 months, and 12 months after intervention. The primary outcome was the VAS score, and the secondary outcome was the BPI score. Besides, the effective rate, adverse effects, and medication consumption were also measured. Stratification analysis was performed to evaluate the therapeutic effect at different disease courses and lesion locations. The risk factors of postherpetic neuralgia were analyzed by logistic regression. Results: 25 patients (19.08%) with herpes zoster continued to have pain in the initially affected area after three months. The VAS scores and the BPI quality of life scores of patients with herpes zoster-associated pain were significantly reduced at 2 weeks, 3 months, 6 months, and 12 months after the intervention. CT-guided radiofrequency thermocoagulation combined with adriamycin injection can improve the pain and quality of life of postherpetic neuralgia patients with short-term efficacy and safety. Age, diabetes mellitus, immune-related diseases were risk factors of postherpetic neuralgia. Conclusions: Early intervention of herpes zoster could significantly improve the pain degree and life quality of patients and influence the occurrence of postherpetic neuralgia. Advanced age, diabetes, and immune-related diseases are risk factors of postherpetic neuralgia.